Expert System For Early Detection Of Attention Deficit Hyperactive Disorder (ADHD) At Soeprapto Psychiatric Hospital Using The Certainty Factor Method - Aprilia Dwi Gumay; Herlina Latipa Sari; Ila Yati Beti (Jurnal Media Computer Science, 2026)
ADHD (Attention Deficit Hyperactive Disorder) is a mental disorder that causes children to have difficulty concentrating, as well as impulsive and hyperactive behavior. ADHD generally appears in children under 12 years of age, but ADHD that occurs in children can be carried into adulthood. This condition can impact a child's achievement if not treated early. Soeprapto Mental Hospital is one of the specialized hospitals that provides facilities and infrastructure in mental health and drug services for the community in Bengkulu Province. Based on the results of observations conducted at Soeprapto Mental Hospital Bengkulu, an average of 2-5 children per month are found to experience ADHD. One way to diagnose this disorder is to consult with an expert. The Expert System for Early Detection of Attention Deficit Hyperactive Disorder (ADHD) at Soeprapto Mental Hospital Using the Certainty Factor Method was created using the PHP programming language and MySQL database, and can be accessed online through the link https://adhdrsjksoepraptobkl.online/. This expert system for early detection of Attention Deficit Hyperactive Disorder (ADHD) can help the public, especially in Bengkulu Province, to consult by entering the patient's symptoms to obtain information on early detection of Attention Deficit Hyperactive Disorder. Based on testing conducted using the black box method both offline and online, it was found that the application's functionality ran well in terms of input, output, and the applied CF method. From the results of alpha testing conducted at Soeprapto Mental Hospital, it can be concluded that this expert system application can be a solution in the process of early identification of ADHD symptoms so that it can be used as a further consideration and faster intervention.